Challenges and Opportunities for Islamic Education in the Digital Era - Asih Tri Lestari; Didan Faisal; Dinda Adila Aprina; Sherinda Wibowo Putri; Yayat Hidayat (International Journal of Religion, Humanity and Cultural Heritage, 2025)
In the digital age, Islamic education is encountering both hurdles and chances. Advancements in technology necessitate Islamic education to evolve and cater to the digital generation, who heavily depend on technological gadgets in their day-to-day routines. Challenges include the digital divide, varying technological literacy and resistance to change in learning methods. However, the digital era also offers opportunities to expand access to education, increase interactivity in learning and facilitate intercultural collaboration. This research uses a descriptive qualitative approach with literature analysis to explore the challenges and opportunities in Islamic education in the digital era. The results show that with the right strategy, Islamic education can utilise technology to improve the quality of education and learners' character. The digital age allows students to control their education by using online resources, but they need critical thinking skills to use information responsibly. Embracing digital tools can help Islamic education face challenges and create a more inclusive learning environment. Hence, Educators must improve their technological skills to integrate digital tools into teaching.